Meta-Analysis of NUDT15 Genetic Polymorphism on Thiopurine-Induced Myelosuppression in Asian Populations - Khaeso, Kanyarat; Udayachalerm, Sariya; Komvilaisak, Patcharee; Chainansamit, Su-on; Suwannaying, Kunanya; Laoaroon, Napat; Kuwatjanakul, Pitchayanan; Nakkam, Nontaya; Sukasem, Chonlaphat; Puangpetch, Apichaya; Tassaneeyakul, Wichittra; Chaiyakunapruk, Nathorn (Frontiers in Pharmacology, 2021)
Backgound: The high incidence of thiopurine-induced myelosuppression in Asians is known to be attributable to genetic variation in thiopurine metabolism. A quantitative synthesis to summarize the genetic association with thiopurine-induced myelosuppression in Asians was therefore conducted. Methods: A literature search of NUDT15 associated studies on thiopurine-induced myelosuppression from January, 2016 to May, 2021 was performed. Two reviewers independently extracted the following data: the author’s name, year of publication, ethnicity, drugs, diseases, genetic polymorphisms, onset, type of myelosuppression and results of Hardy-Weinberg equilibrium. The Newcastle-Ottawa Scale was used to assess the quality of the studies. The pooled odds ratios (OR) and 95% confidence intervals (CI) were calculated to evaluate the associations of NUDT15 and the risk of thiopurine-induced myelosuppression stratified by onset and type of myelosuppressive. Subgroup analysis by NUDT15 genetic polymorphisms was performed. Results: The overall OR for the relationship between NUDT15 genetic polymorphisms and thiopurine-induced early onset of leukopenia and neutropenia in Asian populations were 11.43 (95% CI 7.11-18.35) and 16.35 (95% CI 10.20-26.22). Among NUDT15 polymorphisms, NUDT15*3 showed a significantly increased risk of early leukopenia (OR 15.31; 95% CI 9.65-24.27) and early neutropenia (OR 15.85; 95% CI 8.80-28.53). A significantly higher thiopurine-induced early neutropenic risk was also found for NUDT15*2 (OR 37.51; 95% CI 1.99-708.69). Whereas, NUDT15*5 and NUDT15*6 variants showed a lower risk of leukopenia. Conclusion: This study suggests that NUDT15*3 and NUDT15*2 are important genetic markers of thiopurine-induced early onset of myelotoxicity in Asians, therefore, early detection of these variants before initiating thiopurine therapy is necessary.